Fintech and Payments Regulation : Analytical Framework - Khiaonarong, Tanai (IMF Working Papers; Working Paper ;, 2020)
Financial technology (Fintech) has prompted authorities to consider their potential financial stability benefits, risks, and effective regulation. Recent developments suggest that regulatory approaches and their legal foundations need to augment entity-based regulation with increasing focus on activities and risks as market structure changes. This paper draws on recent international experiences in modernizing legal and regulatory frameworks for payment services. An analytical framework based on a four-step process is proposed-(i) identifying payment activities; (ii) licensing entities and designating systems; (iii) analyzing and managing risks, and (iv) promoting legal certainty. As payment activities evolve and potential systemic risks heighten, adherence to international standards and additional regulatory requirements should be warranted.